2016
DOI: 10.1073/pnas.1612262113
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C increases viral mimicry induced by 5-aza-2′-deoxycytidine

Abstract: Vitamin C deficiency is found in patients with cancer and might complicate various therapy paradigms. Here we show how this deficiency may influence the use of DNA methyltransferase inhibitors (DNMTis) for treatment of hematological neoplasias. In vitro, when vitamin C is added at physiological levels to low doses of the DNMTi 5-aza-2′-deoxycytidine (5-aza-CdR), there is a synergistic inhibition of cancer-cell proliferation and increased apoptosis. These effects are associated with enhanced immune signals incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
189
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 179 publications
(204 citation statements)
references
References 49 publications
9
189
2
Order By: Relevance
“…Others recently showed that vitamin C selectively kills KRAS and BRAF mutant colorectal cancer cells by targeting GAPDH (Yun et al, 2015). Vitamin C treatment of various cancer cell lines also enhances the viral mimicry response to DNA methyltransferase inhibitors such as 5-azacytidine (Liu et al, 2016). Given the diversity of α-KG and Fe 2+ -dependent enzymes that utilize vitamin C as a co-factor (including prolylhydroxylases, jumonji histone demethylases, and TET enzymes) (Young et al, 2015), the mechanistic basis for vitamin C action could well depend on the type of cancer and/or its dependence on specific dioxygenases.…”
Section: Discussionmentioning
confidence: 99%
“…Others recently showed that vitamin C selectively kills KRAS and BRAF mutant colorectal cancer cells by targeting GAPDH (Yun et al, 2015). Vitamin C treatment of various cancer cell lines also enhances the viral mimicry response to DNA methyltransferase inhibitors such as 5-azacytidine (Liu et al, 2016). Given the diversity of α-KG and Fe 2+ -dependent enzymes that utilize vitamin C as a co-factor (including prolylhydroxylases, jumonji histone demethylases, and TET enzymes) (Young et al, 2015), the mechanistic basis for vitamin C action could well depend on the type of cancer and/or its dependence on specific dioxygenases.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this proposition, it has been found that a high proportion of cancer patients are actually deficient in vitamin C [84]. Interestingly, in vitro modeling experiments have shown that vitamin C amplifies the anticancer effects of decitabine, a drug commonly used in treatment of hematological malignancies and well-described driver of DNA demethylation [85]. It will be important to explore this initial work with mechanistic understanding of how future science group Special Report Hore vitamin C (and decitabine) interact with cancer cells, and ultimately, advanced testing in a clinical setting where ascorbate delivery and pharmacokinetics can be effectively controlled.…”
Section: Reprogrammingmentioning
confidence: 94%
“…The reduction of plasma Vitamin C levels in leukemia, as predicted by Stone, is due to an increased uptake and utilization by the actively proliferating leukocytes, leading to tissue biochemical scurvy and consequent increased tendency to bleeding and infections, which are the hallmark of this pathological condition [9,10]. Interestingly, low plasma levels of Vitamin C, have been, very recently, found in around 30% of cases of Non-Hodgkin Lymphoma (NHL), particularly in patients with high bulk disease [11].…”
Section: Contributing To the Synthesis Of Catecholamines;mentioning
confidence: 99%